The Resource-Based View of the Firm in Two Environments: The Hollywood Film Studios From 1936 to 1965 - Miller, Danny; Shamsie, Jamal (Academy of Management Journal, 1996)
This article continues to operationally define and test the resource-based view of the firm in a study of the major U.S. film studios from 1936 to 1965. We found that property-based resources in the form of exclusive long-term contracts with stars and theaters helped financial performance in the stable, predictable environment of 1936-50. In contrast, knowledge-based resources in the form of production and coordinative talent and budgets boosted financial performance in the more uncertain (changing and unpredictable) post-television environment of 1951-65.